Connections of Self-Esteem and Gang Membership - Miller, Annette C. (1997)
Reasons for gang membership have been hypothesized but very little empirical research has been conducted trying to determine why individuals join and remain in delinquent gangs. Low self-esteem has been suggested as a reason for entering into delinquency and joining a gang. Research has shown gang members have lower overall self-esteem than do non-gang individuals (Wang, 1994). An enhancement in this low self-esteem has been suggested as a reason for continuing with gang membership and delinquent behavior. There are mixed results in the research examining the connection of delinquent behavior and increased self-esteem. Kaplan's (1975) self-esteem enhancement theory has not been tested empirically to find out if an increase in self-esteem is a reason for continuing as a gang member. Because delinquency and gang membership are interrelated, the present study will examine Kaplan's self-esteem enhancement theory as a reason for continuing with both gang membership and delinquent behavior. The cross sectional data from is a diverse national sample of eighth grade students. All of the hypotheses are based on the theory that continued gang membership and delinquency will increase self-esteem. First, overall self-esteem measures of gang members and non-gang individuals are compared. Second, it is hypothesized that the higher overall self-esteem levels will be found for those members with longer time investments in a gang. Third, a new measure of place in the gang, which is trying to determine a possible structure for gangs, will be examined for validity. The measure will then be used to determine if members reporting to be close to the center of the gang have higher overall self-esteem levels than those reporting to be near the outside of the gang. None of these hypotheses using Rosenberg's overall self-esteem measure support Kaplan's self-esteem enhancement theory. In recent years, the concept of overall or global self-esteem has been divided into domain specific areas. Research has related school, peer and homebased self-esteem to delinquency and gang membership (Spergel, 1995). The present study employs a gang-specific self-esteem scale in order to examine Kaplan's self-esteem enhancement theory. This scale directly asks the gang member if his or her gang is connected to his or her self-assessment. The sample of gang members agreed that the gang was influential in having positive self-esteem. Then, the gang-specific scale is compared to Rosenberg's overall self-esteem measure. The two scales were found to be negatively correlated. Next, the gang-specific self-esteem scale is examined using the same hypotheses as was done with the overall measure. Kaplan's self-esteem enhancement theory was supported when self‐esteem was assessed with the gang-specific scale